Process optimization in rubber injection moulding manufacturing / Ng Yeow Chian - Ng, Yeow Chian (2019)
Rubber injection moulding is a process of moulding the rubber to produce an applicable product in the manufacturing industry today. Rubber injection moulding which is, a compound strips of rubber fed into the screw barrel of the injection machine, then the material is injected into the mould cavity, with controllable parameters: speed, pressure and temperature. The objective of this research is to optimize the process which are: faster in cycle time, saving material and maintaining products quality. Process optimization is a method to help manufacturers on process improvement in production efficiency and products accuracy. Taguchi method is a technique to define control factors in the process optimization. Taguchi orthogonal array is used to select a combinations of multiple factors at multiple levels. Signal-to-noise ratio (S/N ratio) is used to compares the highest and lowest level of desired, in the control factors of process optimization. The one-way analysis of variance (ANOVA analysis) is used to define statistically significant differences between means of three or more groups’ data. The results of the experiment showed process optimization in rubber injection moulding that can reduce cycle time and material, and also sustaining products quality